Analysis of Student Misconception on Geometry Concepts Using Three-Tier Diagnostic Test - Ratna Istiyani; Arif Muchyidin; Hendri Raharjo (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract : This study aims to determine (1) the results of students misconception analysis on mathematics subjects on the concept of geometry fields, (2) know the percentage of students who misconception on the concept of geometry using Three-Tier Test. Data collection testicles include interview guides and Three-Tier Test questions. Data analysis was done descriptively quantitative. The results showed that 24.1% of students mastered the concept, while the remaining 6.2% of students guessed or did not believe in the answers, 22.2% of students did not understand the concept and 47.5% of students experienced misconceptions. Students experiencing the lowest misconception on the subconscious solve the problem of triangle proposition and line segment 36,5% and the highest misconception experienced by the student on subconcept describes symmetry and angle 59,5%. While the sequence of the third category of misconception highest to lowest on the concept of Geometry Field that occurred is as follows: pure misconception (22%), false positive (17.9%), and false negative (7.6%).Keywords: misconception, three-tier test, false positive, false negative Analisis Miskonsepsi Siswa pada Konsep Geometri Menggunakan Three-Tier Diagnostic TestAbstrak : Penelitian ini bertujuan untuk mengetahui: (1) hasil analisis miskonsepsi siswa pada mata pelajaran matematika pada konsep geometri bidang, dan (2) mengetahui besar persentase siswa yang mengalami miskonsepsi pada konsep geometri bidang menggunakan Three-Tier Test. Subjek penelitian adalah siswa SMA MIPA kelas X sejumlah 43 orang. Insrumen pengumpulan data meliputi pedoman wawancara dan soal Three-Tier Test. Analisis data dilakukan dilakukan secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa 24,1% siswa menguasai konsep, sedangkan sisanya 6,2% siswa menebak atau tidak percaya diri atas jawaban, 22,2% siswa tidak paham konsep dan 47,5% siswa mengalami miskonsepsi. Siswa mengalami miskonsepsi terendah pada subkonsep menyelesaikan masalah dalil segitiga dan segmen garis 36,5% dan miskonsepsi tertinggi yang dialami siswa pada subkonsep menjelaskan kesimetrian dan sudut 59,5%. Urutan ketiga kategori miskonsepsi tertinggi hingga terendah pada konsep Geometri Bidang yang terjadi adalah sebagai berikut:miskonsepsi murni (22%), false positive (17,9%), dan false negative (7,6%).Kata Kunci : miskonsepsi, three-tier test, false positive, false negative